Pengembangan Buku Panduan Praktikum Teknologi Ramah Lingkungan pada Konteks Solar Cell Berbasis Sistem Otomatis Lampu Taman untuk Meningkatkan Berpikir Kritis Siswa - Agus Setyowati; Rendy Wikrama Wardana; Afrizal Mayub (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the validity of the MTs environmentally friendly technology practicum guidebook in the context of using solar cells that have been developed. The research method used is quantitative descriptive to determine the quality or suitability of the environmentally friendly technology practicum guidebook. This practical guidebook explains its feasibility through validity by experts and educators, as well as MTs teachers. The instrument used was a questionnaire which was analyzed using a Likert scale. The research results show that this practical guidebook is suitable for use with a result of 93.3, which is included in the appropriate category and can improve students' critical thinking by calculating using an N-gain of 0.83. Also, the teacher's response to the environmentally friendly technology practicum guidebook on the use of solar cells obtained a percentage of 91.50 in the almost complete category. Meanwhile, student responses obtained a percentage of 89.9 with almost all categories. In conclusion, the validation results that have been carried out on the environmentally friendly technology practicum guidebook on the use of solar cells have very feasible feasibility criteria. Also, students' critical thinking abilities after being given a practicum guidebook for environmentally friendly technology increased. Keywords: Practical Guidebook, Solar C